Fluorination on non-photolabile dppz ligands for improving Ru(ii) complex-based photoactivated chemotherapy. Issue 32 (23rd July 2019) - Boerhan, Rena; Sun, Weize; Tian, Na; Wang, Youchao; Lu, Jian; Li, Chao; Cheng, Xuexin; Wang, Xuesong; Zhou, Qianxiong
Abstract : Fluorination on the retaining ligand of Ru(ii ) PACT agents enhanced phototoxicity but diminished dark cytotoxicity compared with the parent complex, more favorable for PACT application. Abstract : Ru(ii ) polypyridine complexes which can undergo photo-induced ligand dissociation and subsequent DNA covalent binding may potentially serve as photoactivated chemotherapeutic (PACT) agents. In this paper, three fluorinated dppz ligand coordinated Ru(ii ) complexes (2–4 ) containing four monodentate pyridine ligands were studied. All complexes released one pyridine and covalently bound to DNA upon 470 nm irradiation. Compared with the parent complex [Ru(dppz)(py)4 ] 2+ (1 ), 2–4 displayed enhanced phototoxicity but diminished dark cytotoxicity, more favorable for PACT application. Complex3 is the most efficient one with IC50 values of about 8 μM toward HeLa and SKOV-3 cell lines, and also has a much higher IC50 value toward normal L-02 cells. Our results indicate that fluorination on the retaining ligand may be an efficient way to improve the drug activity of Ru(ii ) PACT agents.